Sequencing wasp venom peptides by endopeptidase digestion and nested collision-induced dissociation/post-source decay methods - Hisada, M.; Konno, K.; Itagaki, Y.; Naoki, H.; Nakajima, T. (Wiley-Blackwell, 2002)
A method incorporating nested collision-induced dissociation/post-source decay (CID/PSD) combined with endopeptidase digestion is described as an approach to determine the sequence of N-terminally modified peptides. The information from immonium and related ions observed in the CID/PSD spectrum was used for the selection of a suitable endopeptidase for the digestion of peptides. Rapid and reliable assignment of peptide sequence was performed by the comparison of CID/PSD spectra of both intact and endopeptidese-digested peptide fragments, since the assignments of the observed fragment ions to either N- or C-terminal ions can thus be carried out unambiguously. This nested CID/PSD method was applied to the sequence determination of two peptides from the solitary wasps Anoplius samariensis and Batozonellus maculifrons (pompilid wasps), which could not be sequenced by the Edman method due to N-terminal modification. Copyright (C) 2002 John Wiley Sons, Ltd.